The Analysis of Students’ Critical Thinking Ability with Visualizer-Verbalizer Cognitive style in Mathematics - Buaddin Hasan (SAINTIS Publishing, 2019)
This study aimed to describe the process of critical thinking of students in solving mathematical problems in algebraic viewed from the differences in cognitive styles-Verbalizer Visualizer. The description of the thinking process was based on Polya’s problem-solving indicator namely understanding the problems, developing plans, implementing problem-solving activities, and to re-examining the results obtained. The research instrument includes the researcher himself, tests of cognitive style, problem-solving task, and the interview guideline. The data analysis was performed by means of data reduction, data presentation, interpretation of data, and drawing conclusions. The study concluded that the visualizer subject disclosed the acknowledged information and asked to use the images and algebraic notation, used a variety of strategies to solve problems, performed calculations by taking into account the things we need and recheck the answer in detail. Verbalizer Subject, however, was able to disclose the acknowledged information and questioned using mathematics formula without using pictures and notation. In terms of making plans for the completion, the subject merely used one step-finishing process. In determining the final outcome, verbalizer subject rechecked every step of the finishing by recalling and paying attention to the proper answers